Impact of Temperature on Porcine Liver Machine Perfusion From Donors After Cardiac Death. Issue 10 (18th April 2016) - Nassar, Ahmed; Liu, Qiang; Farias, Kevin; Buccini, Laura; Baldwin, William; Bennett, Ana; Mangino, Martin; Irefin, Samuel; Cywinski, Jacek; Okamoto, Toshihiro; Diago Uso, Teresa; Iuppa, Giuseppe; et al.
Abstract: Normothermic machine perfusion (NMP) has been introduced as a promising technology to preserve and possibly repair marginal liver grafts. The aim of this study was to compare the effect of temperature on the preservation of donation after cardiac death (DCD) liver grafts in an ex vivo perfusion model after NMP (38.5°C) and subnormothermic machine perfusion (SNMP, 21°C) with a control group preserved by cold storage (CS, 4°C). Fifteen porcine livers with 60 min of warm ischemia were preserved for 10 h by NMP, SNMP or CS ( n = 5/group). After the preservation phase all livers were reperfused for 24 h in an isolated perfusion system with whole blood at 38.5°C to simulate transplantation. At the end of transplant simulation, the NMP group showed significantly lower hepatocellular enzyme level (AST: 277 ± 69 U/L; ALT: 22 ± 2 U/L; P < 0.03) compared to both SNMP (AST: 3243 ± 1048 U/L; ALT: 127 ± 70 U/L) and CS (AST: 3150 ± 1546 U/L; ALT: 185 ± 97 U/L). There was no significant difference between SNMP and CS. Bile production was significantly higher in the NMP group (219 ± 43 mL; P < 0.01) compared to both SNMP (49 ± 84 mL) and CS (12 ± 16 mL) with no significant difference between the latter two groups. Histologically, the NMP livers showed preserved cellular architecture compared to the SNMP and CS groups. NMP was able to recover DCD livers showing superior hepatocellular integrity, biliary function, and microcirculation compared to SNMP and CS. SNMP showed some significant benefit over CS, yet has not shown any advantage over NMP.